Single addition of an allyl amine monomer enables access to end-functionalized RAFT polymers via native chemical ligation - Isahak, Naatasha; Gody, Guillaume; Malins, Lara R.; Mitchell, Nicholas J.; Payne, Richard J.; Perrier, Sebastien (Royal Society of Chemistry, 2016)
A novel method for the introduction of a single protected amine-functional monomer at the chain end of RAFT polymers has been developed. This monomer addition, in concert with native chemical ligation, facilitated the development of a simple and versatile method for the end-functionalisation of polymers with peptides.